The Narrative Arc of TATs: Introduction to the JPA Special Section on Thematic Apperceptive Techniques. Issue 3 (4th May 2017) - Jenkins, Sharon Rae
ABSTRACT: The past decade has seen important developments in thematic apperceptive techniques (TATs), with the creation of new card sets having alternate pictures representing different cultures, new scoring systems becoming available, and increasing international communication of these achievements. However, continuing impediments to the development of a validational literature include lingering mistaken assumptions about the nature of story data, ongoing debates about appropriate psychometric evaluation, and continuing questions about how stimuli and scoring systems should be conceptualized and interpreted. Negotiating the publication system can impede some potential authors. Excellent work on TATs with children is not well known in the adult-focused journals. The labor burden of meeting increasingly sophisticated publication standards might be a barrier to assessors focused on clinical practice. Accumulating a focused evidence base is challenging given the diversity of criterion variables for which TATs have been used. Research on TATs by clinicians can span the science–practice gap, but the narrative arc can be a dramatic one. The articles in this special section on TATs represent important conceptual, methodological, and substantive innovations.